Clinical and Biochemical Profile of Acute Liver Failure with Hepatic Encephalopathy in Children from Eastern Nepal - Shah, Gauri Shankar; Singh, Manoj Kumar; Shah, Dheeraj (Journal of Nepal Paediatric Society, 2011)
Introduction: Hepatic encephalopathy is a potentially reversible neurophyschiatric abnormality in the setting of liver failure. Acute liver failure (ALF) is a potentially life-threatening disorder in children. Objectives: The present study evaluated the clinical profile, outcome and factors influencing the outcome of children presenting with acute liver failure and hepatic encephalopathy presenting to a referral hospital of Eastern Nepal. Methodology: Thirty children (17 males and 13 females) were admitted with this diagnosis during two year period.Prospective study. Results: The most common cause of acute liver failure was mushroom poisoning seen in 30% of cases. Only 37% (11 out of 30) children survived, most of them in early stages (Stage I and II) of encephalopathy. Bleeding manifestations were significantly more common (P=0.002) in deaths as compared to survivors. Conclusion: As liver failure is associated with high mortality rates especially in absence of facilities for liver transplantation, efforts should be directed in favor of implementing preventive measures such as vaccination and community education to prevent toxin ingestion. Key Words: Acute liver failure; Hepatic encephalopathy; Mushroom poisoning DOI: 10.3126/jnps.v31i2.4639 J Nep Paedtr Soc 2010;31(2):89-92